Comunicación oficial del GAD Municipal de Babahoyo a través del facebook y su impacto informativo en la población 2020 - Onofre Parra, Marilu Andrea (2020)
The official communications of the GAD of the city of Babahoyo, guide and inform the population about how, when, where and why an activity is going to be carried out through Facebook among other channels. The present study proposes to know what is the information management that the official communications published on Facebook have in the population so that the efficiency of this social network is greater. The response to an interview on the efficiency of Facebook as a communication channel was analyzed by three journalists who practice their profession in different places (radio, written spokesperson and in the GAD of the city of Babahoyo); as well as the responses of the population using a survey published on Facebook. The results of the investigation show that Facebook fulfills its role of officially communicating, where the response of the population is deficient in its attitude of cooperation because they demand their rights but do not fulfill their citizen obligations. The negative position of the opponents who express their discontent in any official publication was also known. In conclusion, lack of motivation and low awareness do not allow the sense of cooperation to be effective, observing an irresponsible attitude in the citizens; Therefore, it is recommended to apply the Briefing strategy, or the elaboration of a contextualized and didactic work plan in which the citizen contributes to community activity and the presence in this Facebook network that responds directly, accurately and quickly to population concerns.